FUNCTIONAL INSTITUTIONAL NETWORKS AS COMMUNITY ASSETS (SOCIAL CAPITAL) FOR SUSTAINABLE MANAGEMENT OF CITARUM WATERSHED - Darwis, Rudi Saprudin; Gutama, Arie Surya; Zainuddin, Moch. (CENTRAL ASIA AND THE CAUCASUS, 2022)
Various parties have handled various problems in the Citarum River and its environment independently or collectively. However, given the complexity and breadth of the problem areas, these efforts require comprehensive environmental management efforts and integrate various programs or activities from various parties. The involvement of various stakeholders, both individual and collective citizens, government agencies and non-government organizations in environmental management of the Citarum River can be effective if the process is built in a network. This study aims to describe the institutional network and its dynamics in the environmental management of the Citarum Watershed (DAS) that show functional relationships. The study was conducted using a qualitative descriptive method for the community in the Sector 7 area of the Harum Citarum Program. Data were collected through in-depth interviews, observations, and focused discussion (FGD) from identified institutions as being in a network in the management of the Citarum watershed. The data collected includes internal and external factors of institutions and networks and influences the shape and condition of institutional networks. The functional relationship between institutions in the network is built based on the interests and suitability of the program orientation. However, formally the Citarum Harum Task Force is the most authorized party to manage the Citarum River.